Trajectories of Depressive Symptoms in Women Prior to and for 6 Months After Breast Cancer Surgery. Issue 2 (June 2014) - Kyranou, Marianna; Puntillo, Kathleen; Aouizerat, Bradley E.; Paul, Steven M.; Cooper, Bruce A.; West, Claudia; Dodd, Marylin; Miaskowski, Christine; Dunn, Laura B.; Elboim, Charles
<x xml:space="preserve">Abstract</x> Depressive symptoms are common in women with breast cancer. This study evaluated how ratings of depressive symptoms changed from the time of the preoperative assessment to 6 months after surgery and investigated whether specific demographic, clinical, and symptom characteristics predicted preoperative levels of and/or characteristics of the trajectories of depressive symptoms. Characteristics that predicted higher preoperative levels of depressive symptoms included being married/partnered; receipt of adjuvant chemotherapy; more fear of metastasis; higher levels of trait anxiety, state anxiety, sleep disturbance, problems with changes in appetite; more hours per day in pain; and lower levels of attentional function. Future studies need to evaluate associations between anxiety, fears of recurrence, and uncertainty, as well as personality characteristics and depressive symptoms.